Parametric Variant Design of Reducer based on Case Based Reasoning - Zhuang Qianyu; Wang Zongyan; Qin Huibin; Dong Hao; Yan Shuai (Jixie chuandong)
In order to improve the efficiency and accuracy of the reducer design,a technology of parametric variant design based on case based reasoning which put case based reasoning technology and the parameter technology of object oriented into the reducer variant design is put forward. A reducer 3D design system is developed by taking Solid Works as a development platform and VB as the development tool,combining the key technology of three dimensional modeling method that combine the feature modeling and parametric design,the nearest neighbor algorithm for computing similarity,and the parametric variant design based on layout sketch.The automatic retrieval,design calculation,model- driven and plot for the reducer is realized,it provides an effective way for the fast intelligent design of the reducer.